Tetraspan TM4SF5-dependent direct activation of FAK and metastatic potential of hepatocarcinoma cells - Jung, Oisun (The Company of Biologists, 2012)
Transmembrane 4 L six family member 5 (TM4SF5) plays an important role in cell migration, and focal adhesion kinase (FAK) activity is essential for homeostatic and pathological migration of adherent cells. However, it is unclear how TM4SF5 signaling mediates the activation of cellular migration machinery, and how FAK is activated during cell adhesion. Here, we showed that direct and adhesion-dependent binding of TM4SF5 to FAK causes a structural alteration that may release the inhibitory intramolecular interaction in FAK. In turn, this may activate FAK at the cell's leading edge, to promote migration/invasion and in vivo metastasis. TM4SF5-mediated FAK activation occurred during integrin-mediated cell adhesion. TM4SF5 was localized at the leading edge of the cells, together with FAK and actin-organizing molecules, indicating a signaling link between TM4SF5/FAK and actin reorganization machinery. Impaired interactions between TM4SF5 and FAK resulted in an attenuated FAK phosphorylation (the signaling link to actin organization machinery) and the metastatic potential. Our findings demonstrate that TM4SF5 directly binds to and activates FAK in an adhesion-dependent manner, to regulate cell migration and invasion, suggesting that TM4SF5 is a promising target in the treatment of metastatic cancer.